Factors Associated with Unplanned Reoperation in Perilunate Dislocations and Fracture Dislocations - Meijer, Sjoerd Th.; Janssen, Stein J.; Drijkoningen, Tessa; Ring, David (Journal of Wrist Surgery, 2015)
Background Perilunate injuries are complex and uncommon injuries that are typically the result of a high-energy injury and are nearly always treated operatively. Little is known about factors associated with unplanned reoperations after surgery for perilunate injuries.Purpose To assess the rate and types of unplanned reoperation after operative treatment of a perilunate dislocation.Patients and Methods We reviewed 115 patients of all ages with unplanned reoperations after operative treatment of perilunate injuries at five hospitals. Planned removal of implants were not considered as unplanned reoperations.Results Sixteen patients had an unplanned reoperation, including four for compartment syndrome (three hand, one forearm); three for deep infection; three for malalignment or an errant screw; two for early salvage procedures; and four for other reasons. We considered seven unplanned reoperations necessary (forearm compartment syndrome, infection, loss of alignment, errant screw) and nine debatable or unnecessary (hand compartment syndrome, early salvage procedures, suspected malunion, etc.). Patients who had an unplanned reoperation were younger (median age 24 versus 34 years; p = 0.0034); had earlier surgery (median days to surgery 0 versus 3; p = 0.0068); and were more likely injured in a motor vehicle collision (50% versus 17%; p = 0.0070). Accounting for interaction among the variables using multivariable analysis, the factors independently associated with unplanned reoperation were young age (odds ratio 0.92) and motor vehicle collision accidents (odds ratio 4.1).Conclusion We conclude that higher-energy injuries may be at greater risk for unplanned reoperation, but more than half of the unplanned reoperations were for debatable indications.Level III Retrospective Cohort Review
Keywords: perilunate dislocations; perilunate fracture dislocations; reoperations; risk factors